PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN TINDAK PIDANA PERDAGANGAN ORANG DALAM PERSPEKTIF KORPORASI SEBAGAI PELAKU - Raden Muyazin Arifin; Jaenuri Jaenuri (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Legal protection for child victims or trafficking in person is still constrained by regulations that are not in favor or victims. From the perspective of the corporation as the perpetrator apparently not much has been touched on criminal responsibility. The victim’s child does get guaranteed legal protection, including restitution, but if the perpetrator does not pay, then there is no way out for the victim provided by Law Number 21 of 2007 concerning the Eradication of trafficking in Persons (PTPPO). Research conducted by Elfina Librine sahetapy from investigations by the National Commission for Child Protection from 2004 to 2006 that occured in Indonesia, which involved various interest including corporations as perpetrators, ilustrates alarming statistics, where trafficking in childreen under the age of five since 2004, the National Commision From Child Protection recorded for 400 cases of child trafficking cited by the national mass media from 2005 – 2006 it is estimated that approximately 10,000 (ten thousand) children were trafficked and 30% or around 3,000 childreen were trafficked for the purpose of prostitution abbroad. The author conducted a normative study on this matter were it was found that childreen as victims of criminal acts of trafficking in persons commited by corporations have not recieved maximum legal protection from the State, government and society, the imposition of fires for corporations is regulated in the Child Protections Act, as well as in the Law on the eradication of the Criminal Act of trafficking in Persons (PTPPO) there is an imbalance that creates gaps.